Healthcare Attitude Towards Using Electronic Medical Records: Meta Analysis - Andry Rachmadani; Heni Elmiani Sari; Ghandys Freecylia (Indonesian Journal of Global Health Research, 2024)
Information and Communication Technology (ICT) in the healthcare system has increased worldwide. EMR system is a digital health technology utilized in the health sector to collect, generate and present health related data by the health professionals along with exchanging information with authorized personnel within the health care setting. This study aimed to analyzed to the healthcare attitude towards using electronic medical records. This was a systematic review and meta-analysis. The PICO research question as follows. The PICO research question as follows population: Healthcare, Intervention: Yes, Comparison: No, Outcome: Using EMR. The article Were obtained from our databases: PubMed and Google Scholar. The Keywords were “Attitude” OR “Health workers” OR “Electronic Medical Record”. Full text article in English with study design cross sectional from 2014 to 2024, were included in this study. The steps of meta-analysis followed PRISMA flow diagram. The article Were analyzed by the Review Manager 5.4. Application a total 5 cross sectional from Ethiopia were selected for a systematic review and meta-analysis. The data collected showed that a good or positive attitude have a willingness to use EMR of 6.32 times compared to health workers who have a bad attitude (aOR = 6.32; CI95% = 4.3 to 9.02). The heterogeneity of the research data shows I2 = 64%, so the data distribution is declared heterogeneous (random effect model).